2017
DOI: 10.1002/hbm.23838
|View full text |Cite
|
Sign up to set email alerts
|

Baseline connectome modular abnormalities in the childhood phase of a longitudinal study on individuals with chromosome 22q11.2 deletion syndrome

Abstract: Occurring in at least 1 in 3,000 live births, chromosome 22q11.2 deletion syndrome (22q11DS) produces a complex phenotype that includes a constellation of medical complications such as congenital cardiac defects, immune deficiency, velopharyngeal dysfunction, and characteristic facial dysmorphic features. There is also an increased incidence of psychiatric diagnosis, especially intellectual disability and ADHD in childhood, lifelong anxiety, and a strikingly high rate of schizophrenia spectrum disorders, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 106 publications
1
6
0
Order By: Relevance
“…As displayed in Table 2 , the most frequent DSM-V diagnoses in 22q-del and 22q-dup were anxiety disorders, autism spectrum disorder, ADHD, and mood disorders. As described previously [ 6 , 55 , 56 ], 22q-del reported more prodromal psychotic symptoms than 22q-dup and HC. However, only four 22q-del were diagnosed with overt psychotic disorder.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…As displayed in Table 2 , the most frequent DSM-V diagnoses in 22q-del and 22q-dup were anxiety disorders, autism spectrum disorder, ADHD, and mood disorders. As described previously [ 6 , 55 , 56 ], 22q-del reported more prodromal psychotic symptoms than 22q-dup and HC. However, only four 22q-del were diagnosed with overt psychotic disorder.…”
Section: Resultssupporting
confidence: 78%
“…In addition, the Structured Interview for Psychosis-Risk Syndromes (SIPS) [ 53 ] was administered to assess for psychotic and prodromal (i.e., psychosis-risk) symptoms. Previous research has suggested that many individuals with the 22q-del present with prodromal symptoms [ 54 ] and up to 25% develop psychosis [ 55 , 56 , 6 ]. 22q-dup, on the other hand, does not have an elevated risk for psychosis [ 14 ], and in fact, there is some evidence suggesting a lower risk for psychosis than in the general population [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Structural neuroimaging studies of children with 22q11DS have reported multiple volumetric brain abnormalities 43,44,81 . A recent study indicated the existence of three subgroups within 22q11DS based on severity of changes in midline structures 82 . The changes we observed in 22q11DS mouse models and Dgcr8 +/− mice were relatively mild and correspond to subgroup 1 or 2 of this classification.…”
Section: Discussionmentioning
confidence: 99%
“…Affected white‐matter bundles mostly include long‐range frontal‐frontal, frontal‐occipital, and fronto‐parietal connections (Kikinis et al, 2016; Olszewski et al, 2017; Roalf et al, 2017; Scariati et al, 2016; Tylee et al, 2017). Only a few studies have thus far examined the characteristics of structural whole‐brain networks (Kikinis et al, 2013; Ottet, Schaer, Cammoun, et al, 2013; Ottet, Schaer, DebbanĂ©, et al, 2013; Padula et al, 2017; VĂĄĆĄa et al, 2016; Zhan et al, 2018), also mostly reporting fronto‐temporal, fronto‐parietal (Ottet, Schaer, Cammoun, et al, 2013; Ottet, Schaer, DebbanĂ©, et al, 2013; Zhan et al, 2018), and limbic dysconnectivity (Ottet, Schaer, Cammoun, et al, 2013; Padula et al, 2015). From a topological perspective, Ottet et al reported longer path lengths and disconnectivity of the brain's hub regions, specifically, in the frontal lobes (Ottet, Schaer, DebbanĂ©, et al, 2013), and VĂĄĆĄa et al (2016) uncovered a “de‐centralization” in 22q11DS with a rerouting of shortest network paths to circumvent an affected core that included frontal, parietal, and subcortical regions.…”
Section: Introductionmentioning
confidence: 99%